Detecção do complexo QRS através de morfologia matemática multiescalar - Saraiva, Aratã Andrade (2012)
This work presents the multiscale mathematical morphology with four scales applied in the ECG signal for detection of the QRS complex. To develop this Biomedical Engineering multidisciplinary work were used knowledge of Cardiology, Electrocardiography, Biostatistics, Biomedical Digital Signal Processing, Signal Detection Theory, ROC Analysis and Performance Classifiers Indexes, interacting with areas of Medicine, Statistics, Mathematics, Computer Engineering and Electrical Engineering. The tests were realized with MIT/BIH ECG signals database. The performance of the method was evaluated using ROC curves and the DER index. The results were compared with the multiscale mathematical morphology of one, two and three scales. In the results was observed that the multiscale mathematical morphology with four scales presented better indexes detection of the QRS complex, confirming its potential in biomedical signal processing, supporting the handling of the QRS complex and offering improvements in detection.